Energy Expenditure and Intensity of Interactive Video Dance Games according to Health Recommendations - Jacek Polechoński; Władysław Mynarski; Wiesław Garbaciak; Artur Fredyk; Michał Rozpara; Agnieszka Nawrocka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
Backround: The aim of this study was the assessment of energy expenditure (EE) and the intensity of physical activity (PA) of adult women during the interactive dance video game (IDVG) Dance Central on Xbox 360 Kinect in the context of health recommendations. Methods: Twenty eight intentionally selected women (mean ± SD age: 21.8±1.1 years, body height: 167.3±6.1cm, body mass: 59.3±5.9 kg, body mass index: 21.2±1.3) met the inclusion criteria and took part in to the experiment. Heart rate monitor, accelerometer, and pedometer were used as measurement tools. Participants performed the same easy dance routine three times (for a total of 10 min.). Trials consisted of imitating the motions presented by the virtual dancer. Results: The data from accelerometer and heart rate monitor were similar, and indicated the moderate intensity of interactive dance video game (IDVG) Dance Central. However, energy expenditure assessed by pedometer was significantly lower. Conclusion: IDVG Dance Central may be useful in increasing the daily dose of physical activity of adult women and meet the health-related recommendations provided its regular practice.